A framework of design thinking: illustrated by an empirical case of prototype innovation. (2015) - Fu, Yu; Liu, Guanzhong
At post-industrial age, design thinking is considered extending to cross-disciplinary collaboration involving various domains. Core of design thinking as a systematic problem solving approach is impelled by the capability of 'design organising'. In China, the realisation of a systematic transformation to knowledge economy calls for new methodologies and educations in design and innovation. The theory of 'prototype innovation' emerged amid this situation. This paper presents an abstract framework with which design organising, prototype innovation and information processing system are integrated to support original design. The framework demonstrates 'structural, inter-subjective, and reflective' characteristics of design thinking and their relationships within the iterative integration process of prototype innovation. An empirical case study is used to illustrate how this framework works in product design. The framework would be valuable for education of organising-typed designers, and for design practices in cross-boundary collaboration under open problems.